Dynamic Characteristic based Structural Optimisation of a Typical UAV Wing - Nambisan, Laneeth; B Kandagal, S; Poojari, Mohan (International Journal of Engineering and Technology, 2018)
Paper presents the modal analysis and rib design part of the project for weight optimization of wing for flutter. Resonance and flutter are important vibration problems. The ribs should be placed such that flutter speed is outside the working speed range. If the flutter speed is well above working speed range, weight optimization can be done to find a balance between the two.Â